Alterações hidrogeomorfológicas devido à dinâmica de uso da terra na Bacia Hidrográfica do Ribeirão Santa Gertrudes (SP) - Paschoal, Letícia Giuliana [UNESP]; Da Conceição, Fabiano Tomazini [UNESP]; Da Cunha, Cenira Maria Lupinacci [UNESP] (My University, 2012)
Agricultural and mining activities are directly related to changes in natural landscapes. From the perspective of anthropogenic geomorphology supported by general systems theory, this research has developed, in order to identify and analyze changes in the land use, mainly from agriculture and the exploitation of clay, and its implications in the hydro-geomorphological characteristics in the Santa Gertrudes Stream watershed (SP). This area is within the context of the Ceramic Pole Santa Gertrudes (SP), which besides its importance as a supplier of raw material, is characterized as the largest center of international reference in ceramic tiles on the American continent. For this purpose, we made land use and geomorphology maps of two scenarios, corresponding to the years 1962 and 2006, which allowed the identification of changes caused by human activities on the landforms of the area, such as the increase in area of parcels intended for mining activity, which went from 3.1% to occupy 19% of the catchment area of the respective period and that, among other changes, gave rise to new forms of relief as, for example, in levels of pit mining abrupt and smooth. The results indicate that the main features of representative of human changes in relief are represented for opening of large clay mining pits and agricultural activities, which intensified the denudation and sedimentation processes in the Santa Gertrudes Stream watershed.
Hydro-geomorphological changes due to dynamics of land use in the Santa Gertrudes Stream Watershed (SP)
Keywords: Anthropogenic geomorphology; Geomorphological mapping; Land use; Santa Gertrudes Stream